Decentralization: A Lever of School Governance in Cameroon - Foche , Asongwe Cyprian (Journal of Innovation in Education and Social Research, 2023)
Decentralization: A Lever of School Governance in Cameroon. According to Hood (2009), Moving towards greater integration of the diverse stakeholders present in education systems, it is worthwhile to consider new approaches to governance, particularly good governance. Good governance approaches involve shifting towards less coercive and less tightly controlled, audited and sanctioned governance mechanisms (Hood and Margretts, 2009). specific research questions guided the study. To what extent does Effective Decentralization Influence School Governance in Cameroon, what are the current Governance practices in the Education sector? How is Governance affecting Decentralization in the Education sector? The statement problem according to observation states that decentralization is practices in most secondary schools in Cameroon, the situation is concerning, particularly in the South-West region, where governance is affected. Despite efforts by the government and international organizations to improve effective school governance and decentralization, statistics show that majority of the schools still do not practice school governance and also practice a high lever of centralize form of governance in the school administration with unequal treatment, in terms of the school achievement, among students with different ethnic background and status. A mixed-methods approach was used, with a sample of 180 teachers. Data was collected using questionnaires and interviews, and analysed using simple linear regression. This study was conducted in Buea sub-division, in the South-West Region of Cameroon The results show that factors such as centralized administration, bad governance, and lack of family support are significant obstacles to school governance. Reason the researcher is interest to investigate decentralization, A lever of school governance in Cameroon.